Effects of Classical Music Therapy on Anxiety Level of Caesarean Section Mother (Medico Legal Update, 2020)
Caesarean delivery will cause mother to experience anxiety. It can cause interference to the physiologicalprocesses in the body. This research aims to find effectiveness of classical music therapy on anxiety levelof casarean section mother at Syekh Yusuf Regional General Hospital, Gowa district, by using HamiltonRating Scale (HARS). This research was an experimental research with a pre-experimental design of onegroup pre-test and post-test design. The sample was 30 caesarean mothers who met the criteria.Based on the results of Wilcoxon rank statistical analysis test, p value = 0,000 and smaller than the ? valuedetermined at 0.05. Therefore, it can be concluded that classical music therapy is effective to reduce anxietylevel of caesarean mothers.